Respuesta :

Answer:

Step-by-step explanation:

Given the expression sin mπ/256 and cos mπ/256

If m = 2;

sin mπ/256 = sin 2π/256

sin 2π/256  =  sin π/128

since 180° = π rad

sin π/128 =  sin 180/128

sin 180/128 = 0.0245

cos mπ/256 = cos 2π/256

cos 2π/256  =  cos π/128

since 180° = π rad

cos π/128 =  cos 180/128

cos 180/128 = 0.9997

If m = 4;

sin mπ/256 = sin 4π/256

sin 4π/256  =  sin π/64

since 180° = π rad

sin π/64 =  sin 180/64

sin 180/64 = 0.04907

cos mπ/256 = cos 4π/256

cos 4π/256  =  cos π/64

since 180° = π rad

cos π/64 =  cos 180/64

cos 180/64 =0.9988

If m = 6;

sin mπ/256 = sin 3π/128

sin 3π/128  =  sin 540/128

sin 540/128 = 0.0736

cos mπ/256 = cos 6π/256

cos 6π/256  =  cos 3π/128

since 180° = π rad

cos 3π/128 =  cos 540/128

cos 540/128 = 0.9973